When is Birth Weight at Term (≥37 wk' Gestation) Abnormally Low? A Systematic Review and Meta-Analysis of the Prognostic and Predictive Ability of Current Birth Weight Standards for Childhood and Adult Outcomes. Issue 1 (March 2016) - Malin, G.L.; Morris, R.K.; Riley, R.D.; Teune, M.J.; Khan, K.S.
Abstract : ( BJOG. 2015;122(5):634–642) It has long been suggested that malnourishment in utero changes fetal programming and alters biological pathways in a way that renders affected neonates more susceptible to disease later in life. Since the first study in 1986 demonstrated an inverse relationship between birth weight and adult cardiovascular disease, many studies have examined associations between low birth weight and morbidity and mortality over the course of a lifetime.